A brief review of vertebrate sex evolution with a pledge for integrative research: towards 'sexomics' - Stöck, Matthias; Kratochvíl, Lukáš; Kuhl, Heiner; Rovatsos, Michail; Evans, Ben J; Suh, Alexander; Valenzuela, Nicole; Veyrunes, Frédéric; Zhou, Qi; Gamble, Tony; Capel, Blanche; Schartl, Manfred; et al. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2021)
Triggers and biological processes controlling male or female gonadal differentiation vary in vertebrates, with sex determination (SD) governed by environmental factors or simple to complex genetic mechanisms that evolved repeatedly and independently in various groups. Here, we review sex evolution across major clades of vertebrates with information on SD, sexual development and reproductive modes. We offer an up-to-date review of divergence times, species diversity, genomic resources, genome size, occurrence and nature of polyploids, SD systems, sex chromosomes, SD genes, dosage compensation and sex-biased gene expression. Advances in sequencing technologies now enable us to study the evolution of SD at broader evolutionary scales, and we now hope to pursue a sexomics integrative research initiative across vertebrates. The vertebrate sexome comprises interdisciplinary and integrated information on sexual differentiation, development and reproduction at all biological levels, from genomes, transcriptomes and proteomes, to the organs involved in sexual and sex-specific processes, including gonads, secondary sex organs and those with transcriptional sex-bias. The sexome also includes ontogenetic and behavioural aspects of sexual differentiation, including malfunction and impairment of SD, sexual differentiation and fertility. Starting from data generated by high-throughput approaches, we encourage others to contribute expertise to building understanding of the sexomes of many key vertebrate species. This article is part of the theme issue 'Challenging the paradigm in sex chromosome evolution: empirical and theoretical insights with a focus on vertebrates (Part I)'.
Keywords: Genome Size; Sex Chromosomes; Male; délka genomu; pohlavní chromozomy; vertebrates; Sex Determination Processes; sex determination; molekulární evoluce; Evolution, Molecular; biologická evoluce; mužské pohlaví; Testis; reproduction; sex chromosomes; Animals; Vertebrates; ženské pohlaví; Biological Evolution; Sex Differentiation; evolution; Ovary; zvířata; testis; genomics; sexuální diferenciace; procesy určující pohlaví; Female; obratlovci; ovarium